2021
DOI: 10.1111/ceo.13969
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in surgical case volume among ophthalmology trainees

Abstract: Background The number of females in ophthalmology has steadily increased over recent decades. The aim of this study was to evaluate whether there is a difference in procedural volume and cataract surgery between male and female trainees in the Royal Australian and New Zealand College of Ophthalmologists (RANZCO). Methods A longitudinal retrospective review of de‐identified surgical RANZCO trainee logbook data from 2008 to 2020 was undertaken. Data from 241 trainee logbooks were analysed for: location of traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…Secondly, previous reports have shown a bias in the number of surgical cases assigned to male versus female surgeons during their training 30. Foley and colleagues reported gender differences in the experience with robotic surgery in colorectal surgery training programmes, with female trainees having fewer opportunities to participate in the use of consoles and to complete the procedures 31.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, previous reports have shown a bias in the number of surgical cases assigned to male versus female surgeons during their training 30. Foley and colleagues reported gender differences in the experience with robotic surgery in colorectal surgery training programmes, with female trainees having fewer opportunities to participate in the use of consoles and to complete the procedures 31.…”
Section: Discussionmentioning
confidence: 99%
“…29 Secondly, previous reports have shown a bias in the number of surgical cases assigned to male versus female surgeons during their training. 30 Foley and colleagues reported gender differences in the experience with robotic surgery in colorectal surgery training programmes, with female trainees having fewer opportunities to participate in the use of consoles and to complete the procedures. 31 They also reported that male supervisors provided fewer opportunities for console participation to female residents than to male residents, but female supervisors provided the same number of console use opportunities to both female and male trainees.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Women continue to be underrepresented in ophthalmology and perform fewer cataract surgeries when compared with men at all stages of experience. [15][16][17] External pressures, such as hyperscrutiny from supervising physicians, who are mostly male, may exacerbate and independently contribute to female surgeons' predilection for disclosure and experienced anxiety. Moreover, women in ophthalmology encounter increased bias, harassment, and discrimination, while female trainees have reported fewer opportunities to perform surgeries and higher levels of bullying.…”
Section: Discussionmentioning
confidence: 99%
“…The sex aspect in medical care is an issue of interest and has further gained importance in recent years. In recent studies by Gupta et al and Gill et al, intraoperative complications in cataract surgery between female and male surgeons in training did not differ significantly [ 37 , 38 ]. Hence, the number of women in surgical subspecialities in ophthalmology and the number of procedures completed by women shows disparities as reported by Gill et al [ 39 ] And this is only one gender inequality, besides women in leadership, academics and research, pay gap, harassment, career satisfaction and mentorship.…”
Section: Discussionmentioning
confidence: 99%